2021
DOI: 10.3389/fped.2021.693583
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Neonatal Resuscitation Training Programme for Healthcare Professionals in Zanzibar, Tanzania: A Pre-post Intervention Study

Abstract: Background: Neonatal mortality rates remain high in Sub-Saharan African countries. Improving the newborn resuscitation skills of healthcare professionals is important in addressing this challenge. The aim of this study was to evaluate a neonatal resuscitation training programme delivered over a two-year period for healthcare professionals in Zanzibar, Tanzania.Methods: A pre- and post-intervention study was designed. We delivered neonatal resuscitation training over a 2-day period in 2017 and 2 days of refresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(43 reference statements)
1
2
0
Order By: Relevance
“…is might be because both studies used manikins as a simulator (similar level fidelity). Our study is also consistent with a study conducted in the resource-limited setting, Zanzibar, that showed improvement of healthcare professionals' knowledge and skills through simulation-based neonatal resuscitation training [3]. is might be the fact that we used the same study design (a pre-post-intervention study) and we both used the same assessment tool (American Heart Association Guidelines) to assess knowledge and clinical skills for neonatal resuscitation among healthcare workers.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…is might be because both studies used manikins as a simulator (similar level fidelity). Our study is also consistent with a study conducted in the resource-limited setting, Zanzibar, that showed improvement of healthcare professionals' knowledge and skills through simulation-based neonatal resuscitation training [3]. is might be the fact that we used the same study design (a pre-post-intervention study) and we both used the same assessment tool (American Heart Association Guidelines) to assess knowledge and clinical skills for neonatal resuscitation among healthcare workers.…”
Section: Discussionsupporting
confidence: 89%
“…A large majority of these deaths occur in low-resource settings. Continuous neonatal resuscitation training based on the local needs in resourcelimited countries is essential to provide con dence in healthcare professionals, to initiate resuscitation and to improve newborn outcomes [3][4][5]. Approximately 5%-10% of newborns require some support to adapt to the extrauterine environment for establishment of regular respiration, and it is already known that neonatal resuscitation training (NRT) of birth attendants using mannequins results in improved knowledge and skills needed for resuscitation but needs to establish the best combination of settings, trainee characteristics, and training frequency to sustain the existing e ect on perinatal mortality reduction [6].…”
Section: Introductionmentioning
confidence: 99%
“…The sample was obtained by using the single population proportion formula with the assumption of proportion ( p ) for nurses and midwives who were working in the labor ward and neonatal units and had performed resuscitation p = 67%. 18…”
Section: Methodsmentioning
confidence: 99%